Sustentación de caso: propuesta de un plan estratégico del ingreso al mercado peruano de una empresa del sector fast fashion - Boero Cespedes, Flavia Mariella (2018)
The present study discusses a strategic plan for entering the Peruvian market of Fast Retailing, with its UNIQLO brand. Fast Retailing is a Japanese business group composed of the companies UNIQLO, GU, Theory, Comptoir des Cotonniers, Princesse Tam Tam and J Brand Operations. It currently maintains operations in Asia Pacific, Western Europe and North America. For the preparation of the preliminary investigation, a diagnosis of the internal and external situation of the company will be carried out, using strategic analysis techniques such as the SWOT matrix, PEST, among others. With this information, a proposal for a strategic plan to enter the Peruvian market will be prepared and its scope will be discussed.